2016
DOI: 10.1016/j.schres.2016.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of engagement in first-episode psychosis

Abstract: Engagement with psychiatric services is critical for ensuring successful outcomes in patients experiencing a first episode of psychosis (FEP). However, it is not known how sociodemographic factors and patient beliefs about the causes of mental illness affect engagement. This study explored predictors of engagement in a cohort of 103 FEP patients presenting to an early-intervention service. Beliefs that mental illness is caused by social stress or thinking odd thoughts predicted higher engagement scores. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
(41 reference statements)
1
19
0
3
Order By: Relevance
“…Specifically, Casey and colleagues (2016) found that believing a mental illness is caused by social stress or having odd thoughts was associated with better treatment engagement scores on the SOLES. It may be that individuals who attribute the development of mental illness to social or environmental aspects rather than to biological reasons experience less stigma, which in turn leads to more openness to and belief in mental health treatment (Casey et al, 2016). Further, it may be that individuals who consider thought processes to be an important part of mental illness etiology may be more receptive to discussing them in treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Casey and colleagues (2016) found that believing a mental illness is caused by social stress or having odd thoughts was associated with better treatment engagement scores on the SOLES. It may be that individuals who attribute the development of mental illness to social or environmental aspects rather than to biological reasons experience less stigma, which in turn leads to more openness to and belief in mental health treatment (Casey et al, 2016). Further, it may be that individuals who consider thought processes to be an important part of mental illness etiology may be more receptive to discussing them in treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Dixon and colleagues (2016) and Doyle and colleagues (2014) discussed the importance of establishing a positive alliance in treatment in order to facilitate adequate participation in services. The therapeutic alliance can be enhanced through the use of specific strategies such as discussing the rationale and goals for treatment, providing care in a supportive and non-judgmental manner, and addressing how treatment aligns with the clients' concerns (Casey et al, 2016;Lal & Malla, 2015;van Schalkwyk et al, 2015). Moreover, employing these recommended strategies within a person-centered, collaborative framework can also produce benefits to the alliance and to the ultimate level of compliance and participation in services (Dixon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…18 PDS : Programme de soins. 19 Diagnostics selon les définitions du CIM10. 20 ECT : Électroconvulsivothérapie.…”
Section: Programme De Soin (Pds)unclassified
“…Compliquée d'un vécu stigmatisant (18) , l'acceptation des troubles comme des soins représente une nécessitédifficileà obtenir.Pourtant, la mauvaise observance du traitementseraitune des premières causesde rechute après un PEP (19) . Ces dernièressont fréquentes, concernant jusqu'à 7 patients sur 10 selon les études (20) .…”
Section: Introductionunclassified
“…But what are the factors that might help or hinder this? Casey and colleagues 4 looked at sociodemographic factors and individual beliefs in just over 100 patients with first-episode illness. Ethnicity, gender, age and socioeconomic factors were not significantly correlated with engagement; however, patients with no qualifications were better engaged than those educated to a higher level.…”
mentioning
confidence: 99%